2021
DOI: 10.3389/fimmu.2021.743422
|View full text |Cite
|
Sign up to set email alerts
|

BNT162b2 Vaccination Elicits Strong Serological Immune Responses Against SARS-CoV-2 Including Variants of Concern in Elderly Convalescents

Abstract: Elderly residents of long-term care facilities (LTCFs) have long been underrepresented in studies on vaccine efficacy, particularly in light of currently emerging variants of concern (VOCs). In this prospective observational cohort study, we analyzed serological immune responses in 190 individuals before, 3 weeks after 1st and 3 weeks after 2nd vaccination with BNT162b2. Unvaccinated COVID-19-convalescent subjects served as reference. End points comprised serum anti-spike IgG and IgA titers as well as neutrali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 31 publications
5
19
0
Order By: Relevance
“…Yet, this observation emphasizes the need for long-term surveillance for the emergence of new variants carrying mutations favoring escape to current population immunity by regular SARS-CoV-2 viral load and genomic monitoring. Finally, given the importance of the humoral immune response for clinical recovery (11), plasma therapy from convalescent vaccine-boosted donors remains a rational option, since it is unexpensive and logistically easy to organize, and contains high titers of neutralizing antibodies against SARS-CoV-2 associated to a broad antigenic spectrum (61-63).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, this observation emphasizes the need for long-term surveillance for the emergence of new variants carrying mutations favoring escape to current population immunity by regular SARS-CoV-2 viral load and genomic monitoring. Finally, given the importance of the humoral immune response for clinical recovery (11), plasma therapy from convalescent vaccine-boosted donors remains a rational option, since it is unexpensive and logistically easy to organize, and contains high titers of neutralizing antibodies against SARS-CoV-2 associated to a broad antigenic spectrum (61-63).…”
Section: Discussionmentioning
confidence: 99%
“…In line with these observations, escape from polyclonal plasmas likely involves larger antigenic structural changes than escape from monoclonal Abs, targeting single epitopes (54). As comparable viral evolution patterns were given the importance of the humoral immune response for clinical recovery (11), plasma therapy from convalescent vaccine-boosted donors remains a rational option, since it is unexpensive and logistically easy to organize, and contains high titers of neutralizing antibodies against SARS-CoV-2 associated to a broad antigenic spectrum (61)(62)(63).…”
Section: Only a Minority Of Patients Unable To Mount An Endogenous Hu...mentioning
confidence: 92%
See 1 more Smart Citation
“…Efficient vaccination of this population is thus not only in the personal interest of each elderly individual him- or herself, but also in the public interest, since the risk for the evolution of potentially hazardous viral mutations in each individual may be lower, if infections with SARS-CoV-2 are overcome as rapid as possible. This is particularly true in long-term care facilities (LTCFs) with their increased risk for outbrakes ( 5 , 6 ) and involvement of younger health care workers, who can easily spread viruses with newly accumulated, potentially hazardous mutations. Several studies confirmed the anticipated effectiveness of COVID-19 vaccines among elderly individuals over 60 years of age ( 6 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly true in long-term care facilities (LTCFs) with their increased risk for outbrakes ( 5 , 6 ) and involvement of younger health care workers, who can easily spread viruses with newly accumulated, potentially hazardous mutations. Several studies confirmed the anticipated effectiveness of COVID-19 vaccines among elderly individuals over 60 years of age ( 6 11 ). Currently, a particular focus lies on the Omicron variant (B.1.1.529), which was first identified in November 2021 in South Africa and Botswana, and which hosts a so far unprecedented number of mutations, resulting in extensive immune escape and reduced vaccine effectiveness ( 12 ).…”
Section: Introductionmentioning
confidence: 99%